2015
DOI: 10.1002/sdtp.10191
|View full text |Cite
|
Sign up to set email alerts
|

40.2: Efficiency Enhancement in Phosphorescent and Fluorescent OLEDs Utilizing Energy Transfer From Exciplex to Emitter

Abstract: This paper discusses the effectiveness of energy transfer from an exciplex to an emitter in both phosphorescent and fluorescent OLEDs. This energy transfer enhances the efficiency, lowers the drive voltage, and extends the lifetime. The increase in the quantum efficiency of a fluorescent OLED using this mechanism is also analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…With the development of new materials and device architectures, green and red OLEDs have achieved lifetimes in excess of 10 5 hours, which is comparable to the latest technique LED chips and much better than conventional incandescent light bulbs. However, the blue emitters especially highly efficient blue phosphors or TADF materials are still suffering from their inherent efficiency roll‐off and short operational lifetimes which strongly destabilize the reliability of WOLEDs . High excited state energy induced annihilation (or chemical bond decomposition) and relatively long exciton lifetime are considered to be responsible for the inferior lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of new materials and device architectures, green and red OLEDs have achieved lifetimes in excess of 10 5 hours, which is comparable to the latest technique LED chips and much better than conventional incandescent light bulbs. However, the blue emitters especially highly efficient blue phosphors or TADF materials are still suffering from their inherent efficiency roll‐off and short operational lifetimes which strongly destabilize the reliability of WOLEDs . High excited state energy induced annihilation (or chemical bond decomposition) and relatively long exciton lifetime are considered to be responsible for the inferior lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Such energy transfer has been attempted in devices with various emission colors [7][8][9]. It has been also demonstrated that the use of ExTET has led to simultaneous improvements of emission efficiency, driving voltage, and lifetime in red to green phosphorescent devices [10]. However, for blue phosphorescent devices particularly using a dopant with azole skeleton ligands, the application of ExTET is difficult because of the significantly high dopant HOMO level, which results in the formation of an exciplex between the host material and the dopant, instead of between the host material and the assist material.…”
Section: Introductionmentioning
confidence: 99%